Letter from Marvin H. Lewis to Jane Tolmach - Marvin H. Lewis:::::: (1973)
A letter from Marvin H. Lewis, a Judge of the Superior Court, to Jane Tolmach congratulating her on her election to the position of Mayor of Oxnard.